El uso de feromonas en el control de plagas del algodon en Andalucia - Alvarado, M.=700 1 Duran, J.M.; Fernandez, J.; Serrano, A.; De la Rosa, A.
(Es, En)
ilus., 10 ref.
Keywords: PECTINOPHORA GOáYPIELLA; ALGODON; CONTROL DE PLAGAS; FEROMONAS; ESPAÑA